The Puzzle of the Unflinching Civilians: Resilience, Resistance, or Resignation? Understanding Pakistan's National Psyche Amid Protracted Conflict - Fatima, Rida; Zafar, Momal; Rafique, Mamoona; Ibrahim, Zahra (International Journal of Qualitative Research, 2025)
Pakistan is a battle-hardened nation, surviving decades of armed conflict, wars, terrorism, Martial laws, and internal political instability. The current paper explores the collective psychological and sociocultural responses of Pakistani civilians to prolonged exposure to conflict and violence. This study employed a thematic and comparative analysis of 46 peer-reviewed articles, media reports, and conflict studies from Pakistan and similarly affected regions, including Colombia, Afghanistan, Uganda, Syria, and Palestine. Through this lens, six themes emerged: normalization of violence, culturally embedded coping mechanisms, emotional disengagement, trauma silencing, state-media framing of conflict, and post-war identity. This study finds that Pakistan’s public resilience is less a reflection of psychological well-being and more a result of adaptive desensitization and institutional narrative control, where trauma is often reframed through patriotic, religious, or heroic perspectives. Comparative insights suggest that this resilience model happens to be uniquely reinforced by media censorship and militarized identity construction, mirroring patterns within other conflict zones. It can be concluded that Pakistan represents a hybrid trauma-resilience model: outwardly stable but fragmented inwardly; publicly stoic, privately grieving, thereby concealing the deeper layers of trauma. The study contributes to global trauma literature by challenging linear post-conflict recovery models while emphasizing context-sensitive frameworks for identity and resilience under chronic insecurity.